Karakteristik dan Hubungan Pengetahuan Serta Tindakan Stimulasi dengan Perkembangan pada Anak Usia Toddler - Misniarti Misniarti; Sri Haryani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the characteristics and relationship of knowledge and stimulation actions with the development of toddler-aged children in the working area of ​​the Perumnas Health Center. The method used is a descriptive analytical design with a cross-sectional approach. The results showed that 72 (72%) were aged > 25 years and 82 (82%) had secondary education and almost all respondents were unemployed 68 people (68%). There is a significant relationship between maternal knowledge and child development, and maternal stimulation actions are related to child development. The conclusion is that most respondents were aged > 25 years and some had secondary education and more than half of respondents were unemployed. Between maternal knowledge and stimulation there is a significant relationship with the development of toddler-aged children. Keywords: Development, Stimulation, Toddler